Maternal compliance with nutritional recommendations in an allergy preventive programme. Issue 3 (1st March 2002) - Schoetzau, A; Gehring, U; Franke, K; Grübl, A; Koletzko, S; von Berg, A; Berdel, D; Reinhardt, D; Bauer, C P; Wichmann, H-E
Abstract : Aims: To assess maternal compliance with nutritional recommendations in an allergy preventive programme, and identify factors influencing compliance behaviour. Methods: Randomised double-blind intervention study on the effect of infant formulas with reduced allergenicity in healthy, term newborns at risk of atopy. Maternal compliance with dietary recommendations concerning milk and solid food feeding was categorised. Results: A total of 2252 newborns were randomised to one of four study formulas. The drop out rate during the first year of life was 13.5% (n = 304). The rates of high, medium, and low compliance to milk feeding during weeks 1–16 were 83.4%, 4.0%, and 7.5%; the corresponding rates to solid food feeding during weeks 1–24 were 60.0%, 12.1%, and 22.9%. In 5.1% of subjects no nutritional information was available. Low compliance was more frequent among non-German parents, parents with a low level of education, young mothers, smoking mothers, and those who weaned their infant before the age of 2 months. Conclusions: Evaluation of allergy preventive programmes should take into account non-compliance for assessing the preventive effectiveness on study outcome.